TOLERANCE AND LOCAL WISDOM BASED ON LANGUAGE “PITUTUR LUHUR” JAVANASE SOCIETY IN THE ECONOMIC FIELD - Alip Sugianto; Sri Hartono (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022)
Pitutur Jawa or better known as Javanese advice is a Javanese saying that has a high philosophical value in various fields such as economics. Now the existence of noble pitutur many young people who do not understand the meaning and especially the intent of a wise advice. Based on that, this article examines the noble character of the Javanese people in the economic field. The method in this research using descriptive qualitative thinking strategy is phenomenology. The result is that in the noble pitutur language of the Javanese community, there is a value of tolerance and local wisdom in the noble pitutur of the Javanese community. This value is important to be preserved and applied to society in order to build the welfare of the community's life